Olarte complejo cultural y deportivo (2019)
The project is located in the Olarte neighborhood, in Bogotá. Its approach is given from a reading of the place, the territory and different factors of its urban context. The main criteria under which its location is selected is the capacity to integrate the neighborhood and its population with the ?Lago Timiza Park?, the Tunjuelo river and the set of green areas that adjoin it, fulfilling the function of an articulating element. The program is also defined based on this study of the sector, which shows the lack of architectonic equipment in the neighborhood, and the need to create an important relationship with its context. That is why one of the most important proposals of the project is to generate this relationship by seeking interactions between the population of the neighborhood and the city, through culture and sports. The cultural complex consists of three main components, which are the theater, the library and the sports hall. Elements that are articulated through public spaces conceived for the development of outdoor activities such as theater and different sports. The library has a variety of spaces that are characterized by their versatility, and that are in flexible components for the development of different activities. The project is based on two key concepts: transparency, and permeability. In the case of the sports center, contemplation spaces are created around the field, which can be adapted for the development of different activities. The theater opens on the sides to increase its capacity if necessary, and in the back, it opens to a grandstand, which adjoins the edge of the river, to allow concerts and different outdoor cultural activities to take place. These characteristics considerably increase the floating population in the sector, and seek to blur the most demarcated limit, in this case, Villavicencio Avenue.